OS EFEITOS DA EXPERIÊNCIA DE FLUXO NA PERCEPÇÃO DA IMAGEM DAS INSTITUIÇÕES DE ENSINO SUPERIOR SOB A PERSPECTIVA DOS ALUNOS DA EDUCAÇÃO A DISTÂNCIA - Costa, Fabio Reis da (2021)
Advances in the technology boosted the creation of distance education courses (DE) among Higher Education Institutions (HEIs), transforming the educational sector. In face of the increased competitiveness, HEIs seek to adopt strategies that establish a positive image in the minds of their audience and contribute to the loyalty of their students. In this sense, the flow experience is an important concept to be explored, because studies approach that the experience can change the image perception of the observed object. Few studies have explored the relationship between HEI image, flow experience and student loyalty in the online environment. Thus, to bring the knowledge of the flow experience to the discussion on the image of HEIs and exploring its effects in the field of DE, the main objective of this thesis was to propose and testing a model that indicates the effects of the flow experience on the perception of the HEI image, and the HEI image in he loyalty of DE students. For this purpose, a quantitative research was carried out using structural equation modeling, using SmartPLS 3.0® software. The valid sample of 357 respondents was composed of students enrolled in distance education undergraduate courses at public and private Brazilian HEIs. In the final research model, elaborated and tested, flow experience was seen as a complex, multidimensional construction, reflected in nine dimensions. Loyalty was approached from a contingency point of view, incorporating behavioral and attitudinal measures related to loyalty. In turn, the image of the HEIs was measured considering the overall view of the construct. The results indicate that there is a positive and significant influence of the flow experience on the image of HEIs. Likewise, the results suggest that there is a positive and significant impact of the image of HEIs on the loyalty of EaD students. The study contributes to a refinement of both the understanding of the image of HEIs and the flow of experience, both in the context of distance education. In addition, based on theory, the study provides a measurement model that allows the identification of the relative importance of each of the constructs under analysis, deepening the knowledge about the relationship between them. The evidence from the study contributes to the advance in the establishment of strategies that can enhance the positive effects of the image for HEIs, as well as in the expansion of the use of marketing in the educational sphere.